On the Problems of Strategic Development of Tourism in the Regions of Russia (Case of the Krasnodar Region and the Resort City of Sochi) - Sorokin, Dmitry Evgenievich; Sharafutdinov, Vladimir Nasibullovich; Onishchenko, Elena Vasilyevna (Economy of Regions, 2017)
We article deals with the problems of strategic development of tourism in the economy of the Russian regions. Wiese problems arise in the period of transition from regulatory functions of the market to the management of long-term development based on the strategic objectives and flagship projects that can achieve these goals in practice. In such a case, the tourism sector of the regional economy is suggested to be considered not within the narrow framework of the tour operator and hotel business activity as it takes place in Russia, but on the much broader scale involving 50 branches of the modern economy as it is increasingly used worldwide. We authors’ hypothesis comes from the fact that in modern conditions, the development and implementation of the strategies of the recreation and tourism industries in the Russian regions can only be effective through the creation and promotion of large diversified knowledge-based competitive regional tourism products at new technological level. We paper clearly demonstrates the group methods of regional strategic planning such as brainstorming and foresight (forecasting and future shaping). We results of the research substantiate not only the need to amend the legislative framework and the current management system of the Russian tourism, to actively elaborate and implement the regional development strategies, to carry out tourism development studies aimed at its commercial success but also the importance of convincing representation of the civilizational advantages of the Russian world and Russian civilization through the tourism.